Plenty too much Chinese food: variation in adjective and intensifier choice in native and non-native speakers of English - Dunn, Robert Lowell (Kansas State University, 2012)
Adjective use and intensification by native speakers of English has been the subject of much study, yet intensification strategies used by non-native speakers have received relatively less attention. The present study compares adjective use by five native English speakers with that of five English L2 speakers at Kansas State University in order to describe in detail how learner patterns of use differ from those of native speakers living in the same community. From conversational data, adjectives were extracted and analyzed for linguistic features such as adjective class, and use of intensification. Results quantify how the non-native speakers have access to a smaller set of adjectives than native speakers, and how those sets differ. Interestingly, the L2 speakers intensify their adjectives at a higher rate than native speakers, again employing a smaller set. The types of adjectives used by the two groups differed in significant ways, with native speakers using more precise, contextually-specific evaluative adjectives such as crappy, elite, retarded, and obsessed, while non-native speakers used more generic adjectives such as happy, nice, long, and famous. The generalized nature of these adjectives, as well as the smaller number of lexemes at the non-native speakers’ disposal, may account for the increased rate of intensification shown by the non-native speakers. Specifically, the depth and complexity of meaning required for conversational interaction is more often handled by native speakers via a variety of specialized adjectives, while non-native speakers must rely more on adjective intensification in order to convey subtle differences in meaning. These results help us better understand how advanced learner language compares to native use. Implications for English language teaching include, but are not limited to, new insight into the types of adjectives taught for conversational English, explicit teaching of intensification strategies, and teaching learners how to construct compound adjectives.
Keywords: English; Learner; Variationist; Adjective; Intensifier; Language, Linguistics (0290); Language, Modern (0291)